2020
DOI: 10.21632/irjbs.13.3.249-267
|View full text |Cite
|
Sign up to set email alerts
|

Past Behaviour, Conscientiousness Personality, and Attitude Toward Engagement in Workplace Affair

Abstract: The phenomenon of workplace romance is an integral part of organizational dynamics. Workplace romance might result in both positive and negative effect. The negative side of workplace romance bears the phenomenon of workplace affair, in which workers engage in extra-marital relations with each other. This research aims to test whether past behaviour, conscientiousness personality, which a part of big five model personality traits and attitude have an impact on the likelihood of employee’s engagement in the wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…Research in other TAM fields on the use of voice e-mail found that perceived ease of use has a between the two variables is significant, or it can be said that the H5 hypothesis is accepted. The same result was also found in the research by Syaebani et al (2020), that there is a tendency when having experienced it will also be followed by behavioral intention because there is an impact from the previous background. A person's intention to accept and adopt E-Money as a means of payment is measured by their level of knowledge about usury .…”
Section: Discussionsupporting
confidence: 83%
“…Research in other TAM fields on the use of voice e-mail found that perceived ease of use has a between the two variables is significant, or it can be said that the H5 hypothesis is accepted. The same result was also found in the research by Syaebani et al (2020), that there is a tendency when having experienced it will also be followed by behavioral intention because there is an impact from the previous background. A person's intention to accept and adopt E-Money as a means of payment is measured by their level of knowledge about usury .…”
Section: Discussionsupporting
confidence: 83%